2005
DOI: 10.1186/1476-4598-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Multiple Endocrine Neoplasia type 1 (MEN1, OMIM 131100) is an autosomal dominant disorder characterized by endocrine tumors of the parathyroids, pancreatic islets and pituitary. The disease is caused by the functional loss of the tumor suppressor protein menin, coded by the MEN1 gene. The protein sequence has no significant homology to known consensus motifs. In vitro studies have shown menin binding to JunD, Pem, Smad3, NF-kappaB, nm23H1, and RPA2 proteins. However, none of these binding studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The fold changes observed were relatively modest, ranging from 0.47 (downregulated in WHO-3) to 2.26 (upregulated in WHO-3 group), and did not overlap significantly with genes discussed above by Missiaglia or Duerr et al Since these studies and others 20, 21, 22 using varying genomic expression array platforms have identified different, non-overlapping genes thought to be of importance, we decided to focus our efforts on one important class of genes known to play a role in these tumors using a qPCR based strategy in order to develop a reliable and predictive model. Other reasons for choosing this strategy include the fact that studies comparing qPCR to microarray results have shown and increased sensitivity of the former, that members of the GPCR group emerged as candidates with differential expression in our exon arrays and in Drozdov’s study, and this class of genes is deemed as one of the most promising for development of new therapeutic agents by the pharmaceutical industry 23 .…”
Section: Discussionmentioning
confidence: 56%
“…The fold changes observed were relatively modest, ranging from 0.47 (downregulated in WHO-3) to 2.26 (upregulated in WHO-3 group), and did not overlap significantly with genes discussed above by Missiaglia or Duerr et al Since these studies and others 20, 21, 22 using varying genomic expression array platforms have identified different, non-overlapping genes thought to be of importance, we decided to focus our efforts on one important class of genes known to play a role in these tumors using a qPCR based strategy in order to develop a reliable and predictive model. Other reasons for choosing this strategy include the fact that studies comparing qPCR to microarray results have shown and increased sensitivity of the former, that members of the GPCR group emerged as candidates with differential expression in our exon arrays and in Drozdov’s study, and this class of genes is deemed as one of the most promising for development of new therapeutic agents by the pharmaceutical industry 23 .…”
Section: Discussionmentioning
confidence: 56%
“…Any future studies, should, in addition, assess whether medications or conditions associated with non-specific elevations in neuroendocrine cell numbers, e.g., PPIs, increase transcript expression. Given the similarities in biology (i.e., expression of receptors, pathways involved in secretion, molecular pathways e.g., MEN-I) [71][73] between GEP-NENs and other NENs e.g., pheochromytomas or medullary thyroid cancers, it would be useful to assess whether the PCR test can accurately identify these lesions. The existence of tumors with a significant neuroendocrine component e.g., prostate tumors [74] or colorectal cancers [75], [76], provides additional clinical samples in which to evaluate the efficacy of the PCR test.…”
Section: Discussionmentioning
confidence: 99%
“…The gene expression profile for neuroendocrine tumors in patients with the MEN1 syndrome was recently reported [44]. The syndrome is characterized by neuroendocrine tumors of the parathyroids, pituitary, and pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%